Application of GIS Technology and Sensor Technology in Tunnel Deformation Mapping - Liu, XiangfaLiu (International Journal of Online and Biomedical Engineering (iJOE), 2017)
The purpose of this study is to enhance the role of sensor technology in tunnel deformation mapping. The method is to combine RTK (real-time dynamic difference) algorithm with GIS (Geographic Information Systems) technology. After coordinating transformation of the deformed data that was collected from the test tunnel, the HGMonitor was then employed to solve the problems. The results show that the horizontal accuracy of tunnel deformation monitoring is about 5mm, and the elevation accuracy is about 15mm, which can meet the actual requirements. We also verified that the test data meets the requirements for tunnel deformation mapping accuracy, which can help to improve the safety and reliability of the tunnel structure.